2022
DOI: 10.1039/d1cp05418j
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive stoichiometric studies on the reaction of silicon in HF/HNO3 and HF/HNO3/H2SiF6 mixtures

Abstract: The stoichiometry of the wet chemical etching of silicon in concentrated binary and ternary mixtures of HF, HNO3 and H2SiF6 was comprehensively investigated. A complete quantification of both dissolved and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(45 citation statements)
references
References 48 publications
2
43
0
Order By: Relevance
“…Depending on the amount and thus the heat capacity of the etching mixture, the strongly exothermic reaction causes a more or less strong temperature increase, which can lead to a self-acceleration of the reaction during the etching rate determination. A temperature increase of the etching bath is inevitably accompanied by a change in the stoichiometry of the reaction and, in particular, by a change in the conversion to reactive intermediates 15 and their stability, 17,20,21,23 and thus also influences the underlying etching mechanism. A clear separation between the impact of temperature and reaction mechanism on the etching rate is therefore experimentally unattainable.…”
Section: Influencing Factors On the Results Of Determination Of Etchi...mentioning
confidence: 99%
See 4 more Smart Citations
“…Depending on the amount and thus the heat capacity of the etching mixture, the strongly exothermic reaction causes a more or less strong temperature increase, which can lead to a self-acceleration of the reaction during the etching rate determination. A temperature increase of the etching bath is inevitably accompanied by a change in the stoichiometry of the reaction and, in particular, by a change in the conversion to reactive intermediates 15 and their stability, 17,20,21,23 and thus also influences the underlying etching mechanism. A clear separation between the impact of temperature and reaction mechanism on the etching rate is therefore experimentally unattainable.…”
Section: Influencing Factors On the Results Of Determination Of Etchi...mentioning
confidence: 99%
“…This higher consumption of HNO 3 is attributed to a higher conversion in the side reaction eqn (2) at increased reaction temperature. 15 Effects of the texture of the silicon and the induction period During texturing of untreated sawn (''as-cut'') solar wafers in HF/HNO 3 /H 2 SiF 6 mixtures, Meinel et al observed very high etching rates 25 in the immediate initial phase of etching and thus in the region of saw damage, typically with a depth of 2 to 5 mm. 26,27 With increasing reaction time and the advancing removal of the saw damage, the determined etching rates decrease until finally a reaction rate is observed that is attributed to a constant bulk etching (Fig.…”
Section: Impact Of the Reaction Vessel Materialsmentioning
confidence: 99%
See 3 more Smart Citations